Yasar Abu Ghosh, Jakub Grygar, Marek Skovajsa (eds).: Monotematické číslo Sociální antropologie v postsocialismu [Thematic issue Social Anthropology in Post-Socialism].: Sociologický časopis [Czech Sociological Review] vol. 43 (2007): 1, Prague: Institute of Sociology, Academy of Science, 227 pp, ISSN 1214-813X. - Novotná, Hedvika (Lidé města, 2007)
A review of the book by Yasar Abu Ghosh, Jakub Grygar and Marek Skovajsa.